2021
DOI: 10.3390/molecules26164719
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Aromatization of 4,7-Dihydro-6-nitroazolo[1,5-a]pyrimidines: Synthetic Possibilities and Limitations, Mechanism of Destruction, and the Theoretical and Experimental Substantiation

Abstract: The reaction tolerance of the multicomponent process between 3-aminoazoles, 1-morpholino-2-nitroalkenes, and aldehydes was studied. The main patterns of this reaction have been established. Conditions for the oxidation of 4,7-dihydro-6-nitroazolo[1,5-a]pyrimidines were selected. Previous claims that the 4,7-dihydro-6-nitroazolo[1,5-a]pyrimidines could not be aromatised have now been refuted. Compounds with an electron-donor substituent at position seven undergo decomposition during oxidation. The phenomenon wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Acetic anhydride was used to activate substrate 12b as with CDI, 4-cyanodihydroisoquinolones 19a , b ( Scheme 3 ) were exclusively obtained in moderate yield, presumably, via the oxidation of the respective α-carbanion (formed, in turn, from the initial tetrahydroisoquinolone adduct due to the basic character of imidazole generated from CDI). Interestingly, thorough exclusion of air from the reaction medium by argon purging did not suppress this process, which is likely due to the possibility of nitro compounds self-oxidizing [ 19 ]. Likewise, variation in such reaction parameters as temperature, reaction duration and concentration in compound 19a synthesis did not dramatically alter the outcome of the reaction with CDI.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic anhydride was used to activate substrate 12b as with CDI, 4-cyanodihydroisoquinolones 19a , b ( Scheme 3 ) were exclusively obtained in moderate yield, presumably, via the oxidation of the respective α-carbanion (formed, in turn, from the initial tetrahydroisoquinolone adduct due to the basic character of imidazole generated from CDI). Interestingly, thorough exclusion of air from the reaction medium by argon purging did not suppress this process, which is likely due to the possibility of nitro compounds self-oxidizing [ 19 ]. Likewise, variation in such reaction parameters as temperature, reaction duration and concentration in compound 19a synthesis did not dramatically alter the outcome of the reaction with CDI.…”
Section: Resultsmentioning
confidence: 99%
“…Pogaku et al [101] reported the synthesis of a newly designed series of benzo Recently, Lyapustin et al [102] reported the synthesis of 4,7dihydro-6-nitrotriazolo[1,5-a]pyrimidines derivatives 137 (42-65 %) based on the multicomponent process between substituted 3-aminotriazoles, 1-morpholino-2-nitroalkenes, and aldehydes in the presence of boron trifluoride etherate as acid catalyst using n-butanol as solvent (Scheme 92).…”
Section: Chemistryselectmentioning
confidence: 99%
“…It should be noted that compounds substituted on the N atom of the pyrimidine ring are not reduced under these conditions. [70] A common property of the dihydro derivatives of azolopyrimidines is their ability to heteroaromatize, which can be achieved preparatively by the action of Nbromosuccinimide, [16,18,19,34,35,56,64,66,[73][74][75] Br 2 /HOAc, [35,60,76,77] I 2 , [78] SeO 2 , [35] PhI(OAc) 2 , [79] CrO 3 , [80] NaNO 2 /HOAc (R 1= COOEt), [81] 2,3-dicyano-5,6-dichloro-pbenzoquinone, [72,82,83] Na 2 S 2 O 8 , [84] ammonium cerium (IV) nitrate, [85] potassium permanganate, [86] manganese (IV) oxide [50] (reaction l). Sometimes the dehydration of dihydro derivatives (reaction I) can occur as a secondary process during their synthesis.…”
Section: Chemical Properties Of Dihydroazolopyrimidinesmentioning
confidence: 99%